The Modified Rural Postman Problem in Vehicle Route Optimization - Kozel, Petr; Orlikova, Lucie; Michalcova, Sarka (Communications - Scientific letters of the University of Zilina, 2018)
The submitted paper deals with designing routes of the vehicles, which provide the transport network services. We limit our focus to such tasks, where the priority is the edge service in the transport network and the initial problem is finding an Eulerian path. Regarding to real-life problems, this contribution presents such procedure of solving, which takes into account both the existence of a mixed transport network containing one-way roads and the existence of a wider transport network. In this network, there are only selected edges with possibility of the effective passages. This problem can be solved by the modified Rural Postman Problem assuming the strongly connected network. Linear programming is a suitable tool for designing optimal routes of service vehicles.